The Millennials Metacognitive Assessment toward Flood-Disaster in Semarang City - Erni Suharini; Edi Kurniawan (Indonesian Journal of Geography, 2021)
Disaster management action should be built up through developing metacognitive and action skills. The metacognitive strategy includes aspects of knowledge about when and how to use it by type, specific technique, and response that are assumed related to deal with disasters. Therefore, this study was aimed to assess the metacognitive abilities of millennials who are affected by disasters and its relation to disaster management. This study used an observatory exploration and inventory (EOI) method involving 248 respondents in flood-prone areas in the city of Semarang. Data were obtained using a questionnaire-based Guttman model electronic survey as many as 52 statements to inventory metacognition abilities and 48 statements related to actions in flood disaster management. Data were analyzed using Pearson’s linear and regression analysis. The non-parametric analysis: Kruskal-Wallis test was run to distinguish metacognitive scores in dealing with food-related problems among millennials groups. For metacognitive awareness, the cognition knowledge was higher than controlling knowledge (p < 0.05). The highest score of metacognitive variables was debugging strategy, which represents a corrective attitude. As described in the value of conditional knowledge, the ability to think fast shows that the millennials are quickly responding and understanding how to act. Most of the respondent actively involved in mitigation and rehabilitation as a volunteer in youth-events such us mangrove planting and cleaning plastic-trash in coastal areas. But, lack involvement of millennial in arranging flood-disaster management make less youth’s responsibility during the disaster. It should be overcome to create a comprehensive approach to community-based disaster resilience.